Assessment of Fetal Ultrasound Training for Obstetrics and Gynecology Residents [24I]. Issue 1 (May 2017) - Sulmers, Christine; Diaz-Sylvester, Paula; Cox, Jill; Han, Heeyoung; Delfino, Kristin; Taylor, Funminiyi
Abstract : INTRODUCTION: Accreditation Council for Graduate Medical Education (ACGME) describes "the full range of commonly employed obstetrical diagnostic procedures, including ultrasonography" as one of the critical competencies required for graduation from an Obstetrics and Gynecology (Ob/Gyn) residency. However, prior studies identified a core curriculum deficit in residency programs. We explored these gaps to determine if they are worth addressing through future interventions. METHODS: A needs assessment survey was disseminated to all ACGME-approved Ob/Gyn residency programs in the USA. RESULTS: One-hundred-forty-four residents completed the survey. Of these, 73.6% had an ultrasound curriculum, of which 77.7% was accessible. Sonographers and faculty were rated as the principal educators. Almost half noted no checklist of competencies during their training, despite the fact that 63.2% were assessed via direct patient observations. Most frequent perceived knowledge deficits included: principle of as low as reasonably achievable (ALARA) and effect of frequency on resolution. Most frequent perceived performance deficits were skill in performing the anatomic survey and diagnosing chorionicity/amnionicity. The majority of respondents felt comfortable teaching/supervising basic obstetric ultrasound except anatomy ultrasounds and cervical length. Assessment of proficiency demonstrated weaknesses in the concept of ALARA, effect of frequency on image quality and identification of suitable crown rump length image. Overall, 76.3% desired more obstetric ultrasound training. Lack of first trimester ultrasounds and insufficient time were listed the most common obstacles to education. CONCLUSION: Additional obstetric ultrasound training for Ob/Gyn residents appears necessary. Improvements in designing an accessible curriculum and formally assessing competencies is fundamental for improving Ob/Gyn training programs.